A State-of-the-Art Review: Personalization of Tinnitus Sound Therapy - Searchfield, Grant D.; Durai, Mithila; Linford, Tania (Frontiers in Psychology, 2017)
Background. There are several established, and an increasing number of putative, therapies using sound to treat tinnitus. There appear to be few guidelines for sound therapy selection and application. Aim. To review current approaches to personalizing sound therapy for tinnitus. Methods. A “state-of-the-art” review (Grant and Booth, 2009) was undertaken to answer the question: how do current sound-based therapies for tinnitus adjust for tinnitus heterogeneity? Scopus, Google Scholar, Embase and PubMed were searched for the 10-year period 2006-2016. The search strategy used the following key words: “tinnitus” AND “sound” AND “therapy” AND “guidelines” OR “personalized” OR “customized” OR “individual” OR “questionnaire” OR “selection”. The results of the review were catalogued and organized into themes. Results: In total 165 articles were reviewed in full, 83 contained sufficient details to contribute to answering the study question. The key themes identified were hearing compensation, pitched-match therapy, maskability, reaction to sound and psychosocial factors. Although many therapies mentioned customization, few could be classified as being personalized. Several psychoacoustic and questionnaire-based methods for assisting treatment selection were identified. Conclusions. Assessment methods are available to assist clinicians to personalize sound-therapy and empower patients to be active in therapy decision-making. Most current therapies are modified using only one characteristic of the individual and/or their tinnitus.